Dietary Acid Load: A Novel Nutritional Target in Overweight/Obese Children with Asthma? - Cunha, P. (2019)
Obesity has been repeatedly linked to asthma, and several potential mechanisms have been proposed in the etiologies of the obese-asthma phenotype. Considering that lungs play an important role in systemic pH and acidbase regulation, are a key organ in asthma development, and that nutritional inadequacy of several nutrients and high dietary acid load can affect airway inflammation and reactivity, we aimed to test the hypothesis that dietary acid load may be associated with asthma in children. Data on 699 children (52% females), aged 712 years, were analyzed. Anthropometric measurements were performed to assess body mass index. Dietary acid load was calculated using potential renal acid load (PRAL) equations from a 24 h dietary recall administrated to children. Adjusted PRAL for total energy intake was applied with the use of the residual method. Lung function and airway reversibility were assessed with spirometry. Asthma was defined by a positive bronchodilation or self-reported medical diagnosis with reported symptoms (wheezing, dyspnea, or dry cough) in the past 12 months. After adjustment for energy intake, sex, age, parents education level, and physical activity, positive and significant associations were found between asthma and PRAL [odds ratio (OR) = 1.953, 95% CI = 1.024, 3.730) in overweight/obese children. Our findings suggest that dietary acid load might be a possible mechanism in overweight/obese-asthma phenotype development.